The influence of oxygen conditioning effect on the permeation properties of polyaniline membranes. Issue 15 (1st November 2016) - Stolarczyk, Agnieszka; Domagala, Wojciech; Turczyn, Roman; Januszkiewicz–Kaleniak, Anna; Kempska, Kinga; Krukiewicz, Katarzyna; Gnus, Małgorzata; Lapkowski, Mieczysław
ABSTRACT: The effect of oxygen conditioning on the performance of polyaniline (PANI) membranes is presented and discussed. The presence of the conditioning effect in such kind of polymer matrix was confirmed by measuring a variation in spin concentration using electron paramagnetic resonance (EPR) spectroscopy. The observed decrease in spin concentration indicates the presence of the dissolved oxygen incompletely removed from PANI matrix. After the prolonged contact between oxygen and PANI membrane, a pronounced decrease in membrane's selectivity was observed, which may be explained by the firm and permanent interaction between oxygen molecules and nitrogen paramagnetic centers of PANI and could be considered as a kind of PANI irreversible doping process.